Pharmacogenomics in cancer therapy - Marsh, Sharon (Henry Stewart Talks, 2015)
Pharmacogenomics in cancer therapy, Types and sources of genetic variation, Adverse drug reactions, Techniques to measure genetic variation, Cancer pharmacogenomics and drug selection, Cancer pharmacogenomics and drug toxicity, Irinotecan (CPT-11) pathway, Cancer pharmacogenomics and drug outcomes, Tamoxifen pathway, Uses of pharmacogenomics